PELATIHAN PENYUSUNAN BUKU BESAR, NERACA SALDO, DAN KERTAS KERJA UNTUK SISWA SMA ST. TARSISIUS I - Adang, Ferry; Klarisa, Livia; Melawati, Natasha; Thewatt, Candise; Evelyne, Theresya (Jurnal Serina Abdimas, 2023)
ABSTRACT The accounting function has an essential role in the progress of a company. This is because the results of the accounting function carried out by accountants are fair, accountable, transparent and reliable financial statements. The financial statements are the main indicator of The Company's performance, as well as an instrument for investors to make strategic decisions. There are several important indicators that can be assessed from the financial statements, such as the level of liquidity and solvency of The Company. Accountants are professions which has an important role in the preparation of these financial statements. The accounting profession needs to be fostered and developed for high school students in order to produce the next generation of competent young accountants. The Untar PKM Team views that this coaching can be carried out in the form of Community Service Activities at SMA St. Tarcisius I.This Community Service activity is carried out offline in the form of theoretical presentations and simulations in the form of discussing cases of accounting processes in the real world in the process of posting general ledgers, preparing trial balances, and preparing working papers. The result of this activity is an increase in literacy and basic understanding of the basics of accounting for SMA St. Tarsisius I. This Community Service activity was carried out on Wednesday, October 26, 2022 offline at St. Tarsisius I High School. Keywords: accounting, ledger posting, trial balance, working papers ABSTRAK Fungsi akuntansi memiliki peran yang esensial dalam kemajuan suatu perusahaan. Hal ini dikarenakan hasil dari fungsi akuntansi yang dijalankan oleh akuntan adalah laporan keuangan yang wajar, akuntabel, transparan, dan dapat diandalkan. Laporan keuangan adalah indikator utama kinerja Perusahaan, serta sebagai instrumen bagi investor untuk menempuh keputusan strategis. Terdapat beberapa indikator penting yang dapat dinilai dari laporan keuangan, seperti tingkat likuiditas dan tingkat solvabilitas Perusahaan. Akuntan adalah profesi yang berperan penting dalam penyusunan laporan keuangan tersebut. Profesi akuntan perlu dibina dan dikembangkan untuk siswa SMA dalam rangka menghasilkan generasi penerus akuntan muda yang kompeten. Tim PKM Untar memandang bahwa pembinaan ini dapat dilakukan dalam bentuk Kegiatan Pengabdian Kepada Masyarakat di sekolah SMA St. Tarsisius I.Kegiatan Pengabdian Kepada Masyarakat ini dilakukan secara luring yang dilakukan dalam bentuk pemaparan teori serta simulasi dalam bentuk pembahasan soal kasus atas proses akuntansi pada dunia nyata dalam proses posting buku besar, penyusunan neraca saldo, serta penyusunan kertas kerja. Hasil dari kegiatan ini adalah peningkatan literasi dan pemahaman dasar atas dasar-dasar akuntansi bagi siswa SMA St. Tarsisius I.. Kata Kunci: akuntansi, posting buku besar, neraca saldo, kertas kerja